Caloric Restriction Effect on Proinflammatory Cytokines, Growth Hormone, and Steroid Hormone Concentrations during Exercise in Judokas - Salma Abedelmalek (Oxidative Medicine and Cellular Longevity, 2015)
The aim of this study was to evaluate the effect of caloric restriction on the immune and hormonal responses during exercise in judo athletes. In a randomised order, 11 male judokas (age: 20.45 ± 0.51; height: 1.71 ± 0.3 m; and body weight: 75.9 ± 3.1 kg) participate in this study during a period of weight maintenance (baseline) and after 7 days of caloric restriction (CR). All subjects performed the Special Judo Fitness Test (SJFT) during the two conditions. Values for nutrient intakes were obtained from a 7 d food record kept during a period of weight maintenance and after a 7-day food restriction (−5~6 MJ/day). Our results showed that CR resulted in significant decreases in body weight (P<0.05) and performance (P<0.05). However, heart rate and SJFT index (P<0.05) increase significantly during CR in comparison to baseline. Moreover, exercise leads to a significant increase in testosterone, cortisol, growth hormone (GH), leukocytes, neutrophils, TNF-α, and IL-6, in both CR and baseline conditions. Compared to baseline, TNF-α and IL-6 were significantly higher during CR condition (P<0.05). Additionally, CR leads to an increase in cortisol and GH (P<0.05) and a decrease in testosterone concentrations (P<0.05).